The Phonology of Tamil Loanwords in Malay based on Optimality Theory: (Fonologi Kata Pinjaman Tamil dalam Bahasa Melayu Berdasarkan Teori Optimaliti) (Jurnal Bahasa, 2018)
This study intends to explain the phonological modifications of Tamil loanwords that have been absorbed into Malay language. Tamil loanwords have to undergo some phonological modifications in order to conform to the system of Malay grammar. The grammar differences between Tamil and Malay languages have given rise to the question of which Tamil words have been borrowed by Malay and how new words have been formed to comply with the Malay language system. Thus, this study was conducted to identify Tamil loanwords that have undergone phonological changes when they are incorporated into Malay language as well as to categorize and explain theoretically the type of adaptation that occurs based on the phonological changes of Tamil loanwords. This study utilizes secondary data obtained from Noriah and Selvarani (2015). A total of 381 words have been identified as Tamil loanwords that are used in Malay language. The results of the hierarchical constraint analysis in Optimality theory show that Tamil loanwords in Malay language involved modification at the syllable structure such as degemenation, vowel shortening and syllable deletion.Keywords: Malay, Tamil, loanwords, phonology, Optimality theory